2021
DOI: 10.3389/fmars.2021.717265
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Stony Coral Tissue Loss Disease Induction and Lesion Progression Within Two Intermediately Susceptible Species, Montastraea cavernosa and Orbicella faveolata

Abstract: During the last several decades, Florida’s Coral Reef (FCR) has been impacted by both global and local stressors that have devastated much of its living coral cover. Additionally, since 2014 FCR has experienced a lethal disease outbreak termed stony coral tissue loss disease (SCTLD). Here, we examined SCTLD spreading dynamics within and among fragmented coral colonies and quantified lesion progression rate of two intermediately susceptible species—Montastraea cavernosa and Orbicella faveolata—through induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Lesion appearance and progression in C. natans and D. labyrinthiformis recruits largely matched similar descriptions for adult colonies (FKNMS, 2018;Landsberg et al, 2020;Eaton et al, 2021). Beginning in some recruits of both species after just 48 h of exposure, lesions continued to present in new, previously healthy recruits over time.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Lesion appearance and progression in C. natans and D. labyrinthiformis recruits largely matched similar descriptions for adult colonies (FKNMS, 2018;Landsberg et al, 2020;Eaton et al, 2021). Beginning in some recruits of both species after just 48 h of exposure, lesions continued to present in new, previously healthy recruits over time.…”
Section: Discussionsupporting
confidence: 67%
“…Although the causative pathogen(s) for SCTLD remain unidentified, enrichment of disease-associated bacteria in lesions, along with the efficacy of antibiotics, suggests that bacteria play a role in disease progression (Meyer et al, 2019; Neely et al, 2020; Rosales et al, 2020; Neely et al, 2021b; Clark et al, 2021). Transmission has been shown to occur through direct contact as well as through the water column in neutrally buoyant particles (Aeby et al, 2019; Dobbelaere et al, 2020; Eaton et al, 2021). Williams et al (2021) found that in the Florida Keys, SCTLD disproportionately affected large corals and areas with high species diversity and colony density.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the present study, there were no significant differences between the DL tissue and the DU tissue of C. natans. Therefore, colonies showing signs of SCTLD may have a disrupted microbiome even far away from the lesion, suggesting a systemic effect [55]. It has been reported in other studies that stress, such as heat stress, often has a stochastic effect on the microbial community composition that can result in an increase in the beta diversity [56].…”
Section: Diversity Indicesmentioning
confidence: 95%
“…In Rosales et al [57], for example, Acropora cervicornis exposed to diseased ramets had a higher beta diversity compared to control corals not exposed to disease. Eaton et al [55] also showed that visibly unaffected areas (DU tissue) on diseased corals later showed signs of tissue loss after coral fragments were separated and isolated from the active disease border on the parent colony, and Landsberg et al [30] found lytic necrosis characteristic of SCTLD lesions within some samples of DU tissue, again suggesting that SCTLD may be systemic within coral colonies.…”
Section: Diversity Indicesmentioning
confidence: 99%
“…Supporting this hypothesis is a spatial epidemiology suggestive of a contagion (Muller et al, 2020), corals affected by SCTLD have specific groups of bacteria associated with lesions as detected by molecular assays (Meyer et al, 2019;Rosales et al, 2020;Ushijima et al, 2020), and multiple species of affected corals respond positively to treatments with antibiotics (Neely et al, 2020(Neely et al, , 2021, although this practice does not prevent genesis of additional lesions (Shilling et al, 2021;Walker et al, 2021). Finally, experimental mesocosm studies suggest SCTLD is transmissible (Aeby et al, 2019;Eaton et al, 2021;Meiling et al, 2021).…”
Section: Introductionmentioning
confidence: 99%